Attack and defence modelling for attacks via the speech interface - Bispham, M; Agrafiotis, I; Goldsmith, M (SciTePress, 2019)
This paper presents a high-level model of attacks via a speech interface, and of defences against such attacks. Specifically, the paper provides a summary of different types of attacks, and of the defences available to counter them, within the framework of the OODA loop model. The model facilitates an inclusive conceptualisation of attacks via the speech interface, and serves as a basis for critical analysis of the currently available defence measures.